The Endangered Arctic, the Arctic as Resource Frontier: Canadian News Media Narratives of Climate Change and the North. (August 2016) - Stoddart, Mark C.J.; Smith, Jillian
Abstract : The Arctic is one of the most radically altered parts of the world due to climate change, with significant social and cultural impacts as a result. Using discourse network analysis and qualitative textual analysis of articles published in the Globe and Mail and National Post during the period 2006 to 2010, we identify and analyze key frames that interpret the implications of climate change on the Arctic. We examine Canadian national news media coverage to ask: How does the Arctic enter media coverage of climate change? Is there evidence of a climate justice discourse in relation to regional disparities in the risks and harms of climate change between northern and southern Canada? Climate change in the Arctic is often framed through the lens of Canadian national interests, which downplays climate‐related social impacts that are already occurring at subnational political and geographical scales. L'Arctique est une des régions du monde la plus radicalement altérée par le changement climatique, menant comme résultat des importants changements sociaux et culturels. En utilisant l'analyse des réseaux de discours ainsi que l'analyse textuelle qualitative des articles publiés dans le Globe and Mail et le National Post de 2006 à 2010, nous identifions and analysons des cadres clés qui servent à interpréter les conséquences du changement climatique dans l'Arctique. Nous examinons la couverture des médias nationaux canadiens pour pouvoir demander : comment est‐ce que l'Arctique s'insère dans la couverture médiatique du changement climatique? Est‐ce qu'il y a de la preuve d'un discours de la justice climatique en relation des disparités régionales des risques et méfaits du changement climatique entre le Canada du nord et du sud? Le changement climatique dans l'Arctique est souvent encadré à travers le prisme des intérêts nationaux canadiens, ce qui minimise les impacts sociaux reliés au climat qui se produisent actuellement aux échelons sous‐nationaux politiques et géographiques.